Development plan and health system: coverage and equity (1999)
In the chapter devoted to health, the national development plan for 1998- 2002 presents a set of problems and some administrative and technical solutions, focused on the financial viability of the health system. Nevertheless the plan let aside the structural dimension of the problems that affect the health system. In this paper we examine the structural components regarding the coverage, equity and service delivering.